Awareness of Pregnant Women for COVID-19 Infection - Erhan Okuyan; Emre Gunakan; Sertaç Esin (Baiman Bauntung Batuah Center, 2021)
Covid outbreak has been getting worse and spread affected all over the world. Pregnant patients are also vulnerable to respiratory diseases. We aimed to evaluate the awareness, emotional status, and behavior of pregnant during the COVID outbreak. This study's main benefit is to analyze the knowledge and understanding of pregnant women about the pandemic and draw attention to the prevention issues that need improvement. This research is a prospective observational study that 199 patients subjected to a questionnaire including 29 questions about patient characteristics, pregnancy information, knowledge about COVID19-infection, behavioral and emotional changes. 130 (65.3) of the patients stated an above-average knowledge level. Television was the most frequent information source (75.4%, n:150) and was the only information source for 90 (45.1%) of the patients. Sixty-nine patients used more than one information source. More than one prevention method uses by 149 (75%) of the patients. Washing hands (n:183, 92.0%) and cleaning the house (n:122, 61.3%) were the most preferred methods. Only 55 (27.6%) of the patients used a mask for prevention. 88(44.2%) of the patients stated that they preferred a shorter hospital stay, and 75 (37.7%) of the patients indicated that they postponed or avoided the pregnancy follow-up visits due to the COVID-19 issue. Pregnant women seem to be aware and stressed of COVID-19, but knowledge of what to do seems insufficient. Patients informed of risks of COVID infection, unplanned hospital admission, and chances of avoiding necessary visits and home birth demands.